Siting strategy for co-locating windfarms and radars considering interference constraints. (October 2022) - Sharma, Ashish; Kumar, Ajay; Choudhury, Sushabhan
As the energy sector moves away from use of fossil fuels towards clean renewable energy alternatives, the technical impediment of windfarm interference with radars has dented the deployment of windfarms. This paper provides a step-by-step siting methodology for co-locating windfarms and radars with the support of simulation tools. A procedural framework for co-locating windfarms and radars is suggested. The proposed methodology identifies crucial variables, such as azimuth, frequency, and topographical features affecting the co-existence of radars and windmills. The effect of variables on radar cross-section for feasible radar frequency ranges between 0.1 GHz and 10 GHz is calculated. The siting methodology suggests use of digital terrain maps for evaluating the interference impact due to terrain screening. In case of inextricable circumstances, where radar needs to be sited in high impact zones near windfarms, suitable mitigation techniques are suggested.